Suppression of epileptiform activity by GABAB receptors in wild type and weaver hippocampus ‘in vitro’ - Yanovsky, Yevgenij; Misgeld, Ulrich (Epilepsy research, 2003)
Inhibition by GABAB receptors comprises activation of K+ conductance and inhibition of Ca2+ conductance, thereby reducing action potential dependent transmitter release and silencing neuronal activity. We compared epileptiform activity and its inhibition by the activation of GABAB receptors in homozygous weaver (wv/wv) and wild type (+/+) CA3 neurons disinhibited by GABAA receptor blockade. In wv/wv mice GABAB receptors have lost their ability to activate K+ conductance (J. Neurosci. 18 (1998) 4001). Spontaneous synchronous burst discharges in elevated [K+]o displayed only subtle differences in +/+ and wv/wv slices, except that the GABAB receptor agonist R-baclofen in low concentration (0.1 μM) strongly reduced the frequency of synchronous bursts in +/+ CA3 neurons, but not in wv/wv CA3 neurons. A high affinity GABAB antagonist, CGP55845A (0.5 μM) promoted the incidence of bursts in low [K+]o. Concentration dependence of the reduction of evoked EPSCs was identical in wv/wv and +/+ neurons (IC50=0.3 μM). Amplitudes of evoked IPSCs were reduced by 0.01 μM R-baclofen in +/+, but not in wv/wv CA3 neurons. The effect of the low concentration was abolished by Ba2+, which is known to block Kir conductance. The data suggest that activation of Kir conductance is important for the control of GABA release by GABAB autoreceptors in the CA3 network. We conclude that the loss of a contribution of Kir conductance to GABAB receptor-mediated autoinhibition reduces the inclination towards spontaneous bursts of wv/wv CA3 pyramidal neurons.
Im Titel ist das letzte "B" bei GABAB tiefgestellt
Online 4 December 2002
Gesehen am 08.04.2021